Dunyamaliyeva , Naila - (:unkn) unknown (My University, 2026)
Naila Yasin qizi Dunyamaliyeva graduated from the Azerbaijan University of Civil Engineers (now Azerbaijan University of Architecture and Construction – AzUAC) in 1998 with a Bachelor’s degree in Applied Geodesy and obtained a Master’s degree in Applied Geodesy from the same university in 2000. She began her professional career at AzUAC in 2000 as a Librarian and subsequently worked as a Training Master at the Department of Engineering Geodesy. She began her academic career as an Assistant Lecturer and, following competitive selection, was promoted to Senior Lecturer in 2012. In 2013, the Department of Engineering Geodesy was renamed the Department of Geomatics, where she has continued her academic activities. Since 2020, Naila Dunyamaliyeva has been working as a Senior Lecturer at the Department of Geomatics, Faculty of Transport, at AzUAC. She is the author of 30 scientific articles, one methodological guideline, and one collection of course programmes.